Kesetaraan Gender: Pemberdayaan Pengusaha Perempuan Melalui LKMS - Aan Nasrullah; Moh. Hasim Afandi (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2020)
The aim of this study is to describe and analyze how Islamic microfinance institution can realize genderequality, especially in the economic field, by empowering women entrepreneurs. This study shows that; First,women entrepreneurs are potential customers for how Islamic microfinance institution, this is given that femaleentrepreneurs in Indonesia are still small, and in practice experience many obstacles, including the lack ofnetworks / relationships (lack of business networks), can not meet the banking requirements (Unbankable)and products Less competitive. Second, the existence of how Islamic microfinance institution has severaladvantages compared to other financial institutions: (1) Providing various types of financial services that arerelevant or in accordance with the real needs of the community and are not in conflict with Islamic law, (2)Serving unbankable low-income groups, and (3) Using contextual and flexible procedures and mechanisms.Third, the model of financing for women entrepreneurs that can be carried out by how Islamic microfinanceinstitution to empower women entrepreneurs, including: (i) the Joint Responsibility Model and (ii) Adat-basedFinancing.